Irreversible Electroporation as a Bridge to Liver Transplantation. Issue 1 (January 2019) - Cannon, Robert M.; Bolus, David N.; White, Jared A.
Hepatocellular carcinoma (HCC) in proximity to major hepatic vasculature poses a risk for invasion, which would contraindicate liver transplantation, yet, is difficult to treat with thermal ablation. This study was undertaken to evaluate the feasibility of irreversible electroporation (IRE) as a bridge to transplantation for high-risk tumors. All patients with HCC in proximity to major hepatic vasculature treated with laparoscopic IRE as bridge to transplantation were studied. Patient and tumor characteristics, length of stay, and treatment-related complications were recorded. Tumor response was assessed with CT and explant pathology. Five patients with a median Model for End Stage Liver Disease (MELD) of 13 (7–21) underwent IRE. The median tumor size was 2.7 cm (1.5–3.7 cm). Adjacent structures included the right portal vein, hepatic veins/inferior vena cava (IVC) and left portal vein. Length of stay was one day for all patients. One patient suffered portal vein thrombosis. The transplant occurred at a median of 142 days (47–264) after IRE. Pathologic necrosis ranged from 30 to 100 per cent, without any vascular invasion. Four patients remain alive with no evidence of disease with median follow-up of 403 (227–623) days. The remaining patients died because of transplant-related complications onpost IRE day 297. IRE shows promise as a bridge to liver transplant for high risk HCC in a preliminary series, justifying further prospective evaluation.